Maize (Zea mays) cultivars evaluation for herbage yield and silage quality - BRAR, NAVJOT SINGH; KUMAR, BALWINDER; HUNDAL, JASPAL SINGH; SINGLA, ANKITA; KUMAR, ANIL; VERMA, H K (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during spring 2019 under on farm trials at commercial dairy farms in Tarn Taran district of Punjab (India) under subtropical conditions. The three cultivars of corn (Zea mays L.), i.e. J 1006, PMH 10 and DKC 9108 were evaluated for their silage production potential. The cropping system followed by farmers was paddy-pea-spring maize (Silage making). Fodder yield, factor productivity, net return and economic productivity were recorded higher under maize hybrid PMH 10 which was found at par with hybrid DKC 9108 and significantly higher than cultivar J 1006. Silages prepared from hybrids PMH 10 and DKC 9108 recorded significantly better (P